Has εὐβίοτος in Aristotle’s Historia Animalium ix Been Mistranslated? - Harry, Chelsea (Journal of Ancient Philosophy, 2025)
Le terme εὐβίοτος, « bien vivre », et ses équivalents apparaissent dans les observations d'Aristote sur les oiseaux, dans l'Historia Animalium IX. Cette note de recherche compare la façon dont le terme aristotélicien a été traduit dans les manuscrits grecs, latins et arabes, ainsi que dans les traductions modernes et contemporaines en anglais, français et allemand, et démontre qu'il a été mal traduit, à commencer par les traducteurs humanistes du XVe siècle, Georges de Trébizonde et Théodore Gaza. Les libertés prises dans la surinterprétation du terme aristotélicien ont peut-être obscurci ce qu'il cherchait à communiquer sur les capacités des oiseaux.
Keywords: Art; Epistemology; Literature; Philosophy; dept.phi

John Dewey - Haitos, Alexander (J.B. Metzler eBooks, 2025)
Keywords: Epistemology; Philosophy; Sociology; dept.phi

John Locke - Haitos, Alexander (J.B. Metzler eBooks, 2025)
Keywords: Philosophy; Political science; Sociology; dept.phi

Zeitloser Gegenstand - Haitos, Alexander (J.B. Metzler eBooks, 2025)
Keywords: Philosophy; Political science; dept.phi

Living well in extended reality: Training phronesis and Socratic humility in XR - Gabriels, Katleen; Volkman, Richard (Journal of Moral Education, 2025)
Practical wisdom is the intellectual virtue relating to the ability to fix ends and discern in a concrete circumstance how to achieve those ends. It is cultivated through engagement with experience rather than book learning. However, a whole matrix of convergent technologies, such as headsets, haptic suits, AI-driven chatbots, and extended realities, such as augmented and virtual reality (AR/VR), creates new conditions for training practical wisdom. How can moral educators facilitate practical wisdom in this extended reality (XR)? Drawing on Nussbaum’s account of phronesis, we contend the job of moral education in XR is mostly about ensuring students’ critical engagement. We suggest AI assistants can contribute to this task, so long as these technologies and the people using them manifest Socratic humility ensuring that no single interaction serves as an ‘oracle of truth’, leaving critical thinking and judgment firmly in the hands of the student.
Keywords: Environmental ethics; Epistemology; Extended reality; Humility; Hypocrisy; Pedagogy; Philosophy; Phronesis; Psychology; Social psychology; Sociology; Socratic humility; Socratic method; Theology; Training (meteorology); convergence; dept.phi; phronesis

Team building-it is all about people, the mission, and values - Goralski, M.A.; Górniak-Kocikowska, K. (Technology Entrepreneurship in Theory and Practice: Perspectives in Science and Engineering, 2025)
Keywords: dept.phi